Advances in urology 2014–2015. (July 2016) - Cresswell, Jo; Laniado, Marc; Sinclair, Andrew; Smith, Daron; Venn, Suzie; Williams, Simon; Brewster, Simon
It has become customary that a session is held at the British Association of Urological Surgeons (BAUS) annual meeting, wherein the most important advances in the major urological sub-specialities are summarised by British opinion leaders for the benefit of the core of urologists. It gives us pleasure to present in this paper the topics covered at the BAUS meeting in June 2015, in Manchester, UK.